2001
DOI: 10.1530/eje.0.1440339
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine factors related to changes in total peripheral vascular resistance after treatment of thyrotoxic and hypothyroid patients

Abstract: Objective: Total peripheral vascular resistance (TPR) decreases in thyrotoxicosis and increases in hypothyroidism. Several mechanisms may be involved, including adaptation to changes in heat production and direct non-genomic effects of tri-iodothyronine (T 3 ) on vascular smooth muscle cells. The aim of this study was to see if changes in TPR are related to changes in plasma concentrations of the endothelial hormones adrenomedullin and endothelin-1 as well as other hormones affecting vasculature. Design: A pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 28 publications
4
24
1
2
Order By: Relevance
“…In the present study serum Hcy in hypothyroid rats were significantly higher than those found in the control, also Hcy in hypothyroid rats which treated with folic acid during and after inducing hypothyroidism were insignificantly lower than those found in the hypothyroid rats. This finding is in line with that of Diekman et al [35] nd Ibrahim et al [4] who reported that plasma Hcy concentrations increased in hypothyroidism and decreased in hyperthyroidism the mechanism of thyroid-induced changes in homocysteine metabolism is currently unknown. Adrees et al [36] who observed that total Hcy levels were elevated in patients with subclinical and overt hypothyroidism.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study serum Hcy in hypothyroid rats were significantly higher than those found in the control, also Hcy in hypothyroid rats which treated with folic acid during and after inducing hypothyroidism were insignificantly lower than those found in the hypothyroid rats. This finding is in line with that of Diekman et al [35] nd Ibrahim et al [4] who reported that plasma Hcy concentrations increased in hypothyroidism and decreased in hyperthyroidism the mechanism of thyroid-induced changes in homocysteine metabolism is currently unknown. Adrees et al [36] who observed that total Hcy levels were elevated in patients with subclinical and overt hypothyroidism.…”
Section: Discussionsupporting
confidence: 91%
“…29 Adrenomedullin, a polypeptide of 52 amino acids, is a potent vasodilator transcriptionally regulated by thyroid hormone, and serum levels are increased in thyrotoxicosis. 33 Interestingly, however, Diekman and colleagues 34 demonstrated that although SVR is decreased and adrenomedullin is increased in thyrotoxicosis, restoration of euthyroidism normalized SVR but was not correlated with plasma adrenomedullin levels. In the present study, only T 3 was an independent determinant of SVR.…”
Section: Effects Of Thyroid Hormone On Cardiovascular Hemodynamicsmentioning
confidence: 99%
“…A decrease in peripheral vascular resistance and in diastolic blood pressure may also be related to enhanced NO production and has been Clinical Chemistry 50, No. 1,2004 found in hypothyroid patients treated with thyroxine (23)(24)(25).…”
mentioning
confidence: 97%